O professor-artista como vírus (Revista Apotheke, 2022)
This text assumes itself asan exercise of reflection and critical analysis of the concept, historically andsocially constructed, of the artist- teacher. Therefore, more than brandish arguments in favor or against this concept, we will seek to understand in their tensions, the way it generates anartist-teacher, for what purpose and with what effects. In the limit, we will consider the double figure created by the subject in relation to art and education that, causing an infection into his code of representations, will enhance a transformation of the subject.
Keywords: artist-teacher; visualarts; practicalreflexive; productionofsubjectivities